Pengaruh Latihan Sirkuit Menggunakan Bola Terhadap Peningkatan Daya Tahan Kardiovaskular Di Porma Football Club Kota Malang - Mochtar Agung Ernanto; Fahrial Amiq (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The implementation of a structured and organized circuit training program will yield maximum results in improving cardiovascular endurance. This study focuses on determining the effect of implementing a circuit training program using a ball on improving the cardiovascular endurance of the Porma FC Kota Malang soccer club. This research uses a pre-experimental design with a one-group pretest-posttest design. The entire study population consisted of 85 Porma FC Kota Malang players with various age characteristics. A sample of 22 players aged 15–16 years was selected using purposive sampling. The Porma FC players underwent circuit training using a ball over 16 sessions. Data collection techniques for this study utilized the Multistage Fitness Test (MFT). The data obtained were analyzed using SPSS version 22 software, showing that the variable obtained a significance level of 0.00 (<0.05), indicating that circuit training using a ball has an effect on the process of improving cardiovascular endurance. The average pretest improvement in endurance was 43.40, and the average posttest improvement was 48.90. It can be concluded that circuit training using a ball has a significant effect on improving the cardiovascular endurance of the Porma FC team.